Anterior Ankle Full Thickness Skin Necrosis Treated with Copper Oxide Dressings without Debridement and Skin Grafting – A Case Report - Melamed, Eyal; Rovitsky, Alexei; Roth, Tohar; Borkow, Gadi (Archives of Clinical and Medical Case Reports, 2022)
Full thickness skin necrosis can result from number of causes, including trash emboli, external pressure, burns and severe skin infections and necrotizing fasciitis. Treatment is often dependent on the size and location of the necrotic skin, involvement of adjacent structures, the presence of active infection and the general condition of the patient. The anterior aspect of the ankle is unique in the sense that the structures there (skin, subcutaneous fat, fascia and tendons) are tight without muscles or padding structures to allow healing of skin necrosis without involvement of the deep structures. Therefore, in cases of skin and subcutaneous tissue necrosis the tendons have a very scarce blood underlying facia (e.g. the extensor retinaculum) is often involved, jeopardizing the extensor foot tendons. In such conditions, the treatment normally includes debridement of the necrotic and infected tissues, which often involves resecting the superior extensor retinaculum and the underlying extensors tendons, if they are involved. Since the tendons have a very scarce blood supply, their fate is often doomed either in the first debridement surgery or in the following period. Eventually, the goal of treatment is to fill the area with abundant granulation tissue to afford skin grafting in follow-up surgery. We describe a case in which treatment with Copper Oxide Dressings (COD) prevented infection by its antibacterial activity while at the same time induced debridement of the necrotic fascia and granulation tissue formation. Subsequently rapid epithelization occurred allowing the wound to heal with normal skin and little scar. Thus, the copper dressing enabled to replace debridement and skin graft surgeries and achieve complete healing within 5.5 months with low cost, very little discomfort and full tendon function. We discuss the mechanisms of COD action that enabled this achievement.